Effects of a wobble board-based therapeutic exergaming system for balance training on dynamic postural stability and intrinsic motivation levels - Fitzgerald, D.; Trakarnratanakul, N.; Smyth, B.; Caulfield, B. (Journal of Orthopaedic & Sports Physical Therapy, 2010)
STUDY DESIGN: Randomized controlled trial. OBJECTIVES: To compare the effects of wobble board exercises with and without feedback provided through integrating the wobble board movement into a computer game system, by comparing changes in postural stability and motivation. BACKGROUND: Therapeutic exergaming systems may offer a solution to poor adherence to postural control exercise regimes by improving motivation levels during exercise performance. METHODS: Twenty-two healthy adults, randomly assigned to an exergaming group (n = 11) and a control group (n = 11), completed 12 exercise sessions. Dynamic postural stability was quantified at baseline and follow-up using the star excursion balance test and the dynamic postural stability index during a jump-landing task. Intrinsic motivation was measured at baseline using the Self-Motivation Inventory and at follow-up using the Intrinsic Motivation Inventory. RESULTS: Star excursion balance test scores showed a statistically significant (P<.008) improvement in the posteromedial and posterolateral direction for both groups. No within-group change for the dynamic postural stability index or between-group difference for star excursion balance test or dynamic postural stability index scores were observed. The ìinterest and enjoymentî category of the Intrinsic Motivation Inventory showed significantly higher scores (P<.001) in the exergaming group at follow-up, which was 1 of the 5 Intrinsic Motivation Inventory categories evaluated. CONCLUSIONS: The findings suggest that exercising with the therapeutic exergaming system showed similar improvements in dynamic postural stability and showed a greater level of interest and enjoyment when compared to a group doing similar balance training without the game system. LEVEL OF EVIDENCE: Therapy, level 2b. Related Slides http://www.jospt.org/docLib/20091230_January2010Fitzgerald.ppt